Pengaruh Harga, Social Media, dan Word of Mouth terhadap Keputusan Pembelian Taichan Cantik Mojokerto - Ghozali, Ghozali; Abdillah, Adil; Rachmawati, Eny; Retnowulan, Dinda Tri (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to find out how price, social media marketing, and word of mouth influence purchasing decisions at Taichan Cantik, either partially or simultaneously. Determining the sample in this study used an accidental sampling technique with 90 respondents and used the analytical method used in this research, namely Multiple Linear Regression analysis. Based on the research analysis results, it shows that price variables, social media marketing variables, and word-of-mouth variables have a significant effect, both partially and simultaneously, on purchasing decisions at Taichan Cantik Mojokerto. In addition, to remain competitive with other comparable businesses, Taichan Cantik is expected to maintain and increase its promotions through word of mouth and social media to make customers choose to buy their products. They are also likely to set competitive prices.